Better adherence to the MIND diet is associated with lower risk of all-cause death and cardiovascular death in patients with atherosclerotic cardiovascular disease or stroke: a cohort study from NHANES analysis. Issue 3 (26th January 2023) - Song, Yanjun; Chang, Zhen'ge; Jia, Lei; Song, Weihua; Wang, Hongjian; Dong, Qiuting; Dou, Kefei
Abstract : Subjects with ASCVD or stroke who better adhered to the MIND diet presented a lower risk of all-cause and cardiovascular death, suggesting the MIND diet as a therapeutic dietary pattern with a great value in the secondary prevention of ASCVD. Abstract : The Mediterranean-DASH intervention for neurodegenerative delay (MIND) diet has been evaluated as a brain-protective diet pattern that contributes to better cognitive performance and attenuates dementia. Cardioprotective effects of the MIND diet have been demonstrated in the primary prevention of atherosclerotic cardiovascular disease (ASCVD), however, there is no exploration in patients with ASCVD. In this prospective cohort study, 943 patients with ASCVD or stroke from the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2006 were enrolled and divided into three groups according to the MIND diet scores (≤7.0, 7.5–8.0, and ≥8.5). Compared with patients with low MIND diet scores (≤7.0), patients with better adherence to the MIND diet presented a significantly lower risk of all-cause and CV death, as results showed that the hazard ratio [HR] and 95% confidence interval [CI] were 1.09 (0.78, 1.52) in the group of 7.5–8.0, 0.66 (0.50, 0.87) in the group of ≥8.5 for all-cause mortality ( P trend = 0.002); 0.70 (0.42, 1.17) in the group of 7.5–8.0 and 0.52 (0.35, 0.75) in the group of ≥8.5 for CV mortality ( P for trend < 0.001). Besides, per one-score increase in the MIND diet score was associated with a 10% (HR = 0.90, 95% CI: 0.82, 0.99) lower risk of all-cause mortality and a 16% (HR = 0.84, 95% CI: 0.73, 0.97) lower risk of CV mortality in these patients. In conclusion, this study, for the first time, revealed that better adherence to the MIND diet was associated with improved outcomes in patients with ASCVD.